2001
DOI: 10.1021/bi002658v
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Studies on Endothelial Nitric Oxide Synthase Complexed with Nitric Oxide and Mechanism-Based Inhibitors

Abstract: The crystal structure of the endothelial nitric oxide synthase (NOS) heme domain complexed with NO reveals close hydrogen bonding interactions between NO and the terminal guanidino nitrogen of the substrate, L-arginine. Dioxygen is expected to bind in a similar mode which will facilitate proton abstraction from L-Arg to dioxygen, a required step for O-O bond cleavage. Structures of mechanism-based NOS inhibitors, N(5)-(1-iminoethyl)-L-ornithine and N-(3-(aminomethyl)benzyl)acetamidine, provide clues on how thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 48 publications
(87 reference statements)
8
89
1
1
Order By: Relevance
“…Based on the structure of eNOSoxy complexed with NIO, Poulos and co-workers (17) favored the first heme oxygenase-like mechanism since the methyl carbon of NIO is closest to the B nitrogen of the porphyrin but ϳ4 Å away from the ␣-meso carbon. They suggested that this inactivation mechanism also applies to W1400 and explained the observation that W1400 is an irreversible activator only for iNOS by its higher turnover number compared with eNOS and nNOS (17). Although this may be an important kinetic factor, our structures suggest additional reasons.…”
Section: Figmentioning
confidence: 56%
See 1 more Smart Citation
“…Based on the structure of eNOSoxy complexed with NIO, Poulos and co-workers (17) favored the first heme oxygenase-like mechanism since the methyl carbon of NIO is closest to the B nitrogen of the porphyrin but ϳ4 Å away from the ␣-meso carbon. They suggested that this inactivation mechanism also applies to W1400 and explained the observation that W1400 is an irreversible activator only for iNOS by its higher turnover number compared with eNOS and nNOS (17). Although this may be an important kinetic factor, our structures suggest additional reasons.…”
Section: Figmentioning
confidence: 56%
“…The latter group is held in place by interactions with the hydroxyl groups of Tyr-485/706 (iNOSoxy/nNOSoxy) and the cofactor H 4 B, respectively. The absence of H 4 B in the structure of the eNOS W1400 complex (17) might be the reason why there is only some residual electron density for the 3-aminomethyl group (17). Based on the available data, it …”
Section: Structures Of the N -Propyl-l-arg Complexes-npa Belongs To Tmentioning
confidence: 99%
“…The cDNA sequence encoding full-length caveolin-3 (residues 1-151) was cloned by PCR using the rat skeletal muscle cDNA library (Stratagene, La Jolla, CA) and primers containing BamHI and EcoRI restriction sites for subcloning at the 5Ј-and 3Ј-ends, respectively. Each construct was confirmed by direct sequencing, and the fusion proteins were subsequently expressed in E. coli BL21 (DE3) cells and purified by affinity chromatography using Ni 2ϩ -NTA-agarose, as described by Li et al (37). The GST-caveolin-1 fusion protein was constructed by subcloning the full-length caveolin cDNA into the pGEX4-T-2 expression vector.…”
Section: Methodsmentioning
confidence: 99%
“…Certain fungal CPOs and bacterial P450s have been genetically engineered for large-scale biotransformations (7)(8)(9)(10). The active sites of these three protein families, known in detail from a number of x-ray crystal structures (4,(11)(12)(13), are remarkably similar. All three have an iron-protoporphyrin IX center coordinated to a cysteine thiolate.…”
Section: Oxygen Activation By Heme Proteinsmentioning
confidence: 99%